Design of Single-Phase Active Power Filter for Harmonic Mitigation in Distribution Power Line - Dahidah, Mohamed S. A. (2002)
Recently, the wide use of power electronic components in various application s has affected the quality of the power. One of the most serious problems is that of the harmonic, which is generated from the nonlinear loads such as variable frequency AC motor drives, uninterruptible power supplies (UPSs), personal computers, laser printers, and many more [1-4], is has harmful effect on the electrical equipment. Several techniques have been carried out over the year to prevent the effects of the harmonic [3], [7], The active power filter is the most efficient method, which has been developed in different configuration s to meet the different demands [9]. This thesis presents the design and development of a single-phase shunt active power filter that is suitable for commercial or education al buildings with computer loads [9]. The proposed filter is designed to mitigate the third and fifth order harmonics for two main reasons. Firstly, because of using large number of relatively small single phase loads that may produce excessive total amount of the third harmonic fifth and seventh harmonic [3]. Secondly because of the active power filter rating could be highly reduced when the suppression of one or two special harmonics is effected by the active filter [20].